Faktor pelaksanaan kesehatan reproduksi perusahaan dan dukungan keluarga dalam penentuan pola menyusui oleh pekerja (buruh) wanita di Kabupaten Kudus - Fatimah, Siti; Martini, Martini; Rostyaningtyas, Dewi; Soemarmi, Amiek (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2013)
Background: Indonesia still faces problems of health, especially infant and child mortality rate is quite high. One effort to overcome this problem by promotion of breastfeeding. Family problems arise when workers are women workers give birth and breastfeed. Objectives: This study aimed to determine the pattern of breastfeeding on women workers as well as the factors influencing the feeding patterns.Method: This study used cross sectional analytic survey. The research sample included women workers who had toddlers 2-5 years old and working in the industry in Kudus Regency, totaling 75Â  women workers (laborers) in the Djarum cigarette factory, Aroma and Norojono based and proportional random sampling. Data were collected through interviews using questionnaires and in-depth interviews. Results: The results showed that the majority (70.7%) of subjects had a basic level of education (elementary and junior high school), most (74.7%) was classified as less knowledge, most (53.5%) was classified as less supportive stance, the majority (69,3%) of breastfeeding pattern was quite good, although all subjects not exclusively breastfeed their children. Spearman Rank test showed no relation between education, knowledge, attitude, family support and company policies with breastfeeding pattern. It is advised that the company began planning the establishment of child care support coordination with the Ministry of Social Affairs, and that working women to breastfeed exclusively.Conclusion: There were no relation between education, knowledge, attitude, family support and company policies with breastfeeding pattern.Â Keywords breastfeeding pattern, family support, company support, women workers, cigarette manufacturing